Self-control as a mediator in the relationship between mobile technology usage and social competence - Syed Ahmad Muhajir Alhaddad Syed Esa (2019)
Social competence is important for the development of early adolescence. It has an impact on children's social behavior and their interaction with others. With the advent of mobile technology today, more and more children are using mobile technology devices to socialize with others. Therefore, this study attempts to investigate the influence of mobile technology usage on social competence among early adolescents. In addition, this study also attempts to study the potential of selfcontrol as the mediating variable for the effect of mobile technology usage towards social competence among early adolescents. This is a quantitative study that make use of survey where data is collected via questionnaire. A total of 236 students from three schools in Gombak, Selangor were chosen as respondents in the study by using stratified random sampling with 300 targeted sample. A set of questionnaires is used in this study, comprise of Mobile Phone Problem Use Scale (MPPUS-10) to measure mobile technology usage, Social Competence Scale for Teenager (SCST) to measure social competence and Self-scoring Self-control Scale (SSSC) to measure self-control. The data obtained were analyzed in accordance with the hypotheses formed using three types of tests which are independent t test, correlation and SEM by using IBM Statistical Package for the Social Sciences (SPSS) version 24 and Analysis of a Moment Structures (AMOS) version 22. Results show that mobile technology usage significantly affect social competence negatively, while social competence and self-control are positively correlated. In addition, a full mediation is found as the effect of mobile technology usage on social competence diminished when self-control act as a mediator. Thus, it is evident from this study that mobile technology usage has an impact on social competence and self-control which is important for early adolescents.